Balloons and Stents in the Endovascular Treatment of Cerebral Aneurysms: Vascular Anatomy Remodeled - Piotin, Michel; Blanc, Raphaël (Frontiers in Neurology, 2014)
Wide-neck intracranial aneurysms were originally thought to be either untreatable or very challenging to treat by endovascular means because of the risk of coil protrusion into the parent vessel. The introduction of the balloon remodeling technique (BRT) and later stents specifically designed for intracranial use has progressively allowed these lesions to be endovascularly treated. BRT and stent-assisted coiling technique (SACT) were first designed to treat sidewall aneurysms but, with gained experience and further technical refinement, bifurcation complex-shaped wide-neck aneurysms have been treated by coiling enhanced by BRT and SACT. In this article, we will review and describe the inherent benefits and drawbacks of BRT as well as SACT.